Double-Glide Method Using Cathereep Protective Sheet As a Substitute in Descemet's Stripping Automated Endothelial Keratoplasty - Toshida, Hiroshi; Honda, Rio; Matsui, Asaki; Matsuzaki, Yusuke; Shimizu, Yusuke; Seto, Takahiko; Ohta, Toshihiko; Murakami, Akira (ISRN Transplantation, 2013)
Purpose. For the insertion of the donor graft in Descemet's stripping automated endothelial keratoplasty (DSAEK), the double-glide method using a Busin glide and intraocular lens (IOL) glide concomitantly has been shown to be effective. The aim of this report is to evaluate the results for the double-glide method using Cathereep (Nichiban, Tokyo, Japan), a protective sheet made of polyurethane film for medical use, as a substitute for an IOL glide. Materials and Methods. The subjects were 10 eyes of 10 patients with bullous keratopathy. The DSAEK operation was performed, and the double-glide method was used for the donor graft insertion. During the operation, an IOL glide was used for the 5 eyes, and the Cathereep protection sheet was used for the remaining 5 eyes. We trimmed approximately 5 mm wide strips from the nonadhesive area surrounding the Cathereep protection sheet. Results. The donor graft was inserted equally easily with the Cathereep protective sheet and IOL glides and improvement of visual acuity was noted in both groups significantly. A favorable postoperative course was obtained with no perioperative complications including endothelial damage. Conclusions. Cathereep protective sheet can be used as a substitute for an IOL glide for double-glide method in DSAEK.